آں جنابﷺ سے متعلق مغربی رویوں کا پس منظر: یہود و نصاریٰ کے ابتدائی طرزِ فکر وعمل کا مطالعہ: Background of Western attitudes towards Muhammad: A Study of the early thoughts and practices of the Jews and Christians (Al-Qamar, 2019)
Orientalists play a key role in the identified adversarial Western attitudes and thoughts about Prophet Muhammad (ﷺ), and it is known that the Orientalists working on Islam and Prophet of Islam have been mostly Jewish and Christians. In this perspective, the history of Orientalists’ and Western ideas about the Prophet goes back to the early Jewish and Christian attitude in this regard. So, to understand Western attitude towards Muhammad, it is very important to know the background, and since this background is the early approaches of Jews and Christians, this article attempts to explore these approaches. An examination of the referred early approaches towards the Prophet reveals that attitude of the Jews and Christians at first seemed somewhat positive in some respects, but soon they began to strongly oppose the Prophet. On the one hand, Jews adopted a very hostile attitude; on the other hand, Roman Christians started conflicting. These attitudes became more and more severe in the times to come, until the Crusades and the period of fierce confrontation between Islam and the West, in which hatred and enmity of the West and Jews and Christians towards the Prophet reached its peak.
Keywords: Muhammad; Jews; Christians; early attitudes